EFFECT OF FUEL SUBSIDY REMOVAL ON POULTRY PRODUCTION INPUT IN KWARA STATE, NIGERIA - Adebimpe, M. A.; Salau, S. A.; Ayantoye, K. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the effect of fuel subsidy removal on the cost of major inputs of poultry production and identified the coping strategies adopted by farmers to mitigate these challenges in Kwara State, Nigeria. A three-stage sampling procedure was used to select 201 registered poultry farmers across 11 Local Government Areas. Primary data were collected using well-structured questionnaires and analysed using descriptive statistics, and paired t-test. The results revealed that poultry farming was predominantly male-dominated (83.58%), with farmers relying primarily on personal savings (86.07%) as their source of capital. The mean flock size was 931.52 birds, with 67.66% having regular access to veterinary services. The paired t-test analysis indicated that fuel subsidy removal had statistically significant effects on all major input costs (p<0.05), with feed costs recording the highest increase followed by labour wages, day-old chicks, vaccines, and transportation costs respectively. Furthermore, poultry farmers adopted proactive coping mechanisms, with increasing production scale ranking as the most important strategy, followed by seeking government support and membership of cooperative societies. The study concludes that while fuel subsidy removal imposed significant cost pressures on poultry enterprises, the sector demonstrated remarkable resilience through adaptive strategies. The study recommends targeted government interventions, including input subsidies, and capacity-building programs, to enhance the resilience of poultry farmers in the post-subsidy era.